Voting with public information - Shuo Liu (University of Zurich, Department of Economics, 2017)
We study the effect of public information on collective decision-making in committees, where members can have both common and conflicting interests. In the presence of public information, the simple and efficient vote-your-signal strategy profile no longer constitutes an equilibrium under the commonly-used simultaneous voting rules, while the intuitive but inefficient follow-the-expert strategy profile almost always does. Although more information may be aggregated if agents are able to coordinate on more sophisticated equilibria, inefficiency can persist even in large elections if the provision of public information introduces general correlation between the signals observed by the agents. We propose simple voting procedures that can indirectly implement the outcomes of optimal anonymous and ex post incentive compatible mechanisms with public information. The proposed voting procedures also have additional advantages when there is a concern for strategic disclosure of public information.
Keywords: D72; D82; 330; Strategic voting; collective decision-making; public information; committee design; optimal voting rule; information disclosure